Gluten related disorders : diagnostic approaches, treatment pathways and future perspectives - Rostami-Nejad, Mohammad (Academic Press, 2022)
Gluten-related disorders are prevalent worldwide, especially in developing countries. These diseases have similar clinical manifestations. Although they are characterized by a specific pathophysiological response to ingestion of gluten, differential diagnosis of these disorders is very challenging. Failure to diagnose and treat these disorders at an early stage, can lead to irreparable health and cost damages. Gluten-Related Disorders: Diagnostic Approaches, Treatment Pathways, and Future Perspectives solves this problem by reporting up-to-date scientific findings that allow for faster, more accurate diagnosis of gluten-related disorders as well as guidance on treatment options. By identifying the distinctive features of each of the gluten-related disorders, the chapters lead readers to optimal diagnosis and treatment options as well as better research designs for future research studies on the pathogenesis of these disorders. This reference provided by experts in the field is perfect for researchers, scientists, and medical practitioners who are involved in addressing gluten-related disorders.